2019
DOI: 10.15244/pjoes/103354
|View full text |Cite
|
Sign up to set email alerts
|

Metal Accumulation and Effect of Vitamin C and E in Accumulated Heavy Metals in Different Tissues in Common Carp (<i>Cyprinus carpio</i>) Treated with Heavy Metals

Abstract: Heavy metals are naturally occurring elements on the earth's crust and they are also referred to as trace elements [1]. Some of these metals have found application in many areas of human life, such as agriculture, pharmacy, cosmetics, industry, medicine, etc. Human exploitation of these metals has increased the risk of environmental pollution from them. In view of their toxic properties they can be dangerous to all receiving ecosystems [2]. Sources of heavy metals contamination of aquatic ecosystems can be min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…This is also probably why the highest mean value of 37.55±0.03µg/ml in T4 was obtained in the gills of the fish in this case at the 8 th week of exposure for susteined up-regulation of the defence system of the fish at the highest level of concentration and duration; and that the presence of the vitamin may have reduced the burden in lower concentrations. In line with this, Sahiti et al [34] reported how supplementation of vitamins C and E either alone or jointly had significantly decreased (p<0.01; p<0.05) levels of accumulated heavy metals in investigated tissues compared to the control and exposed groups.…”
Section: Gsh Production Levels In C Gariepinus Exposed To Sub-lethal Concentrations Of Pb Toxicant and The Respective Supplemented Treatmmentioning
confidence: 65%
“…This is also probably why the highest mean value of 37.55±0.03µg/ml in T4 was obtained in the gills of the fish in this case at the 8 th week of exposure for susteined up-regulation of the defence system of the fish at the highest level of concentration and duration; and that the presence of the vitamin may have reduced the burden in lower concentrations. In line with this, Sahiti et al [34] reported how supplementation of vitamins C and E either alone or jointly had significantly decreased (p<0.01; p<0.05) levels of accumulated heavy metals in investigated tissues compared to the control and exposed groups.…”
Section: Gsh Production Levels In C Gariepinus Exposed To Sub-lethal Concentrations Of Pb Toxicant and The Respective Supplemented Treatmmentioning
confidence: 65%
“…Another important finding was that, groups of fish exposed to the same sub-lethal concentrations of ZnO (bulk particles or nanoparticles) and supplemented with vitamins (E + C) have a significant decrease (P0.05) in accumulated Zn levels in muscle and gill tissue compared to groups without supplementation. This may be due to the chelating role of vitamins (E + C) in reducing Zn content in investigated tissues of O. niloticus fish as confirmed by Sahiti et al (2020) who stated that supplementation of vitamins C and E either alone or jointly had significantly decreased (p<0.01; p<0.05) levels of accumulated heavy metals in investigated tissues of common carp compared to the control and exposed groups. Moreover, our results illustrated that the values of accumulated Zn in muscle and gill tissues of supplemented groups returned to similar levels established in the control at low concentrations but still higher than control at the high sub-lethal concentrations of ZnO BPs or ZnO NPs.…”
Section: )mentioning
confidence: 68%
“…Vitamin C has a role in tissue repair, protein formation, inactivation of toxic metals and protection of other vitamins (such as A and E), DNA from the harmful effects of oxidation (Hamza, 2017). In a study conducted by Sahiti et al (2020), it was reported that vitamin C reduced the heavy metal accumulation in the tissues. Due to these properties of vitamin C, various concentrations of vitamin C (25, 50 and 75 ppm) were added to the LB medium containing cadmium, in order to reduce the negative of cadmium.…”
Section: Resultsmentioning
confidence: 99%